Knowledge, Attitude, and Practice Toward COVID-19 Among Sherubtse College Students in Bhutan: A Web-Based Cross-Sectional Study - Dorji, Thinley; Wangmo, Karma; Yezer; Wangchuk, Tashi; Tshokey; Wangdi, Kinley (Frontiers in Public Health, 2021)
Bhutan has reopened schools and colleges after an initial closure to contain COVID-19 transmission. However, the risk of transmissions is higher in schools and colleges due to crowding. Therefore, this study aimed to assess the level of knowledge, attitude, and practice (KAP) towards COVID-19 among students of Sherbutse College in Bhutan. Methods A cross-sectional study using a questionnaire was conducted in September 2020 among the students of Sherubtse College, Bhutan. The questionnaire was made in Google Forms and administered through a social forum WeChat app. KAP scores were calculated including mean scores. The association between the KAP was assessed using the Pearson correlation coefficient. Results A total of 613 students participated in the survey. The majority of the participants (57%) were female and 56% were from the third year. The mean knowledge score was 10.7 (standard deviation [SD]=1.7; range 0-14), mean attitude score of 3.67 (SD=1.0; range: 0-5) and mean practice score of 5.19 (SD=Range: 0-6). A majority of the students had good knowledge (98%) and practice (93.5%) scores, and a positive attitude (86.6%) towards COVID-19. A positive but weak correlation between good knowledge and practice (r=0.1, p=0.0126) was observed. Having a positive attitude led to practicing appropriately most of the time (r=0.1866, p<0.001). Conclusion Students had good KAP scores and followed COVID-19 prevention protocols advocated by the government. Good knowledge and a positive attitude were translated into good practice. Therefore, the Bhutan government’s education campaign seems to be effective in students.